2018
DOI: 10.1200/jco.2018.36.6_suppl.340
|View full text |Cite
|
Sign up to set email alerts
|

CYP11A1 inhibition as a therapeutic approach for the treatment of castration resistant prostate cancer.

Abstract: 340 Background: Castration-resistant prostate cancer (CRPC) is a major cause of cancer mortality worldwide. The mechanisms behind the development of resistance are complex and not fully understood; altered androgen synthesis, androgen receptor (AR) overexpression or gene amplification, and mutations have been indentified. However, tumor growth may still be responsive to therapies that can further suppress de novo intratumoral steroid synthesis upstream of CYP17A1. ODM-208 is an oral, non-steroidal and selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This suggests a reduction in adrenally-derived androgens beyond those achieved by ABI may have clinical benefit in men with CRPC, and is consistent with our observation that tissue androgens and tumor growth were suppressed more strongly by surgical ADX in this study than in previously reported studies using ABI. This suggests that proof-of-concept studies testing agents capable of achieving true ‘non-surgical ADX’ are warranted (such as the recently reported CYP11A inhibitor ODM-208),(69) and that optimal clinical efficacy may be obtained by a combination of CYP11A and CYP17A inhibition. While beyond the scope of the current work, PDX studies testing CYP11A inhibition are planned.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a reduction in adrenally-derived androgens beyond those achieved by ABI may have clinical benefit in men with CRPC, and is consistent with our observation that tissue androgens and tumor growth were suppressed more strongly by surgical ADX in this study than in previously reported studies using ABI. This suggests that proof-of-concept studies testing agents capable of achieving true ‘non-surgical ADX’ are warranted (such as the recently reported CYP11A inhibitor ODM-208),(69) and that optimal clinical efficacy may be obtained by a combination of CYP11A and CYP17A inhibition. While beyond the scope of the current work, PDX studies testing CYP11A inhibition are planned.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of beginning with cholesterol, steroid-sulfates are utilized, imported by fetal/placental transporters SLC22A11, SLC22A19, and SLCO4A1: the 'side-entry' synthetic route. These GBM then utilize AKR1C1 and AKR1C3 for 'backdoor' steroidogenesis [131,134,135,[137][138][139][140]. Tumors lacking this non-canonical importation (asteroidogenic) were identified by low levels of all five gene transcripts.…”
Section: Non-canonical Steroidogenesis the Eanda Groupmentioning
confidence: 99%